PERKEMBANGAN ILMU PENGETAHUAN DAN LANDASAN SOSIAL BUDAYA - Achruh, Andi (Inspiratif Pendidikan, 2018)
Abstract: Education provides the advancement of human thought so that their standard of living increases. In its development from age to age education transformed into a system. An educational system systematically arranged in the Law of the Republic of Indonesia No. 20 of 2003 on the law of the national education system article 11 paragraph 1, which explains that education is implemented through three lines of formal, informal and informal education. These three educational paths are mutually related to each other and need to make the social changes that occur in the future. The existence of education as a factor of social change, the role of educators or teachers have a strategic role in realizing students to be ready in the face of expected social change. As expressed by Amanda Coffey (2001) that educators / teachers from day to day work for schools, as the key to implementation (implementation) of education policy. As the main social actor in education, educators have a responsibility in complementing the pedagogic practice as well as the transmission of knowledge and skills. They are also responsible for the management of the classroom. Educators occupy the leading position in policy and social change